2017
DOI: 10.3727/096504017x14854310794561
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of TRIM44 Inhibits the Proliferation and Invasion in Prostate Cancer Cells

Abstract: Tripartite motif 44 (TRIM44), a member of the TRIM protein family, has been shown to play a role in tumor development and progression. However, the potential involvement of TRIM44 in prostate cancer has not been fully explored. Therefore, in the present study, we analyzed the expression of TRIM44 in prostate cancer and assessed the role of TRIM44 in the progression of prostate cancer. Our results showed that the expression of TRIM44 was significantly upregulated in human prostate cancer cell lines. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 20 publications
3
38
0
Order By: Relevance
“…Kawabata et al demonstrated that TRIM44 knockdown attenuated the tumor necrosis factor-α-dependent phosphorylation of the p65 subunit of nuclear factor (NF)-κB and inhibitor of NF-κBα in breast cancer cells (11). Another study inferred that the knockdown of TRIM44 inhibited the proliferation and invasion of prostate cancer cells through inactivation of the phosphoinositide 3-kinase/Akt signaling pathway (3). A study in China found that TRIM44 may promote proliferation and metastasis in non-small cell lung cancer via the mammalian target of rapamycin signaling pathway (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kawabata et al demonstrated that TRIM44 knockdown attenuated the tumor necrosis factor-α-dependent phosphorylation of the p65 subunit of nuclear factor (NF)-κB and inhibitor of NF-κBα in breast cancer cells (11). Another study inferred that the knockdown of TRIM44 inhibited the proliferation and invasion of prostate cancer cells through inactivation of the phosphoinositide 3-kinase/Akt signaling pathway (3). A study in China found that TRIM44 may promote proliferation and metastasis in non-small cell lung cancer via the mammalian target of rapamycin signaling pathway (6).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that TRIM44 may have an oncogenic role in the invasion and metastases of several types of human cancer, including prostate cancer (3), hepatocellular carcinoma (4), gastric carcinoma (5), non-small cell lung cancer (6) and testicular germ cell tumors (7). However, at present, the precise function of TRIM44 and its underlying carcinogenic mechanism in ovarian cancer remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies have shown that TRIM family proteins may positively or negatively regulate carcinogenesis depending on the types of TRIM or the origin of cancer . Specifically, TRIM44 has been reported in a number of studies showing oncogenic effect in various cancers . Ong et al have reported that TRIM44 overexpression resulted from genomic amplification in 16.1% of all epithelial cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The oncogenic effects of TRIM44 have been reported in a number of studies in various types of cancers . We have previously shown that TRIM44 is involved in carcinogenesis of testicular germ cell tumor and breast cancer .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation